2015
DOI: 10.2106/jbjs.n.00542
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Validity, and Responsiveness of the Western Ontario and McMaster Universities Osteoarthritis Index for Elderly Patients with a Femoral Neck Fracture

Abstract: The results are based on two clinical trials. The questionnaires used concern pure, clinically relevant issues (ability to walk, climb stairs, etc.). Moreover, the results can be used for future research comparing clinical outcomes (or treatments) for populations with a femoral neck fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Therefore, the 36-item WHODAS 2.0 might be more suitable for evaluating cognition and getting along domains in KBD patients. Several studies have shown that the WOMAC is responsive to changes in OA patients with different situations [31][32][33]. A study compared the responsiveness of the WOMAC and generic Short Form-36 (SF-36) in patients with OA of the legs undergoing comprehensive inpatient rehabilitation, and the results showed that both of the measures were able to detect improvement in pain, but the WOMAC was more responsive than the SF-36 in the measurement of function [31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the 36-item WHODAS 2.0 might be more suitable for evaluating cognition and getting along domains in KBD patients. Several studies have shown that the WOMAC is responsive to changes in OA patients with different situations [31][32][33]. A study compared the responsiveness of the WOMAC and generic Short Form-36 (SF-36) in patients with OA of the legs undergoing comprehensive inpatient rehabilitation, and the results showed that both of the measures were able to detect improvement in pain, but the WOMAC was more responsive than the SF-36 in the measurement of function [31].…”
Section: Discussionmentioning
confidence: 99%
“… 2001 , Burgers et al. 2015 ). Cognitive function was evaluated with the Short Portable Mental Status Questionnaire (SPMSQ) (Pfeiffer 1975 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ceiling effects are more commonly reported in all WOMAC subscales, particularly in pain and stiffness . A ceiling effect has been demonstrated in the pain and stiffness subscales when patients are evaluated at 10 weeks and 12 months after hip fracture .…”
Section: Western Ontario and Mcmaster Universities Osteoarthritis Indexmentioning
confidence: 98%
“…Floor effects for WOMAC subscales or total scores are generally minimal or 0 . However, in one 2005 study, floor effects at 6 months and 2 years following THA were significant in the pain (25% and 39%) and stiffness (30% and 46%) subscales .…”
Section: Western Ontario and Mcmaster Universities Osteoarthritis Indexmentioning
confidence: 99%
See 1 more Smart Citation